TMET-09. LOSS OF MAT2A COMPROMISES METHIONINE METABOLISM AND REPRESENTS A VULNERABILITY IN H3K27M MUTANT GLIOMAS. (14th November 2022) - Halbert, Matthew; Golbourn, Brian; Halligan, Katharine; Varadharajan, Srinidhi; Krug, Brian; Mbah, Nneka; Kabir, Nisha; Stanton, Ann-Catherine; Locke, Abigail; Casillo, Stephanie; Zhao, Yanhua; Sanders, Lauren; et al.
Abstract: H3K27-mutant diffuse midline gliomas (DMGs) are defined as grade IV tumors by the World Health Organization. DMGs are inoperable and resistant to chemo/radio therapies. Median survival ranges from 8-11 months, with 2% of patients surviving beyond 5 years. H3K27M mutations lead to global epigenetic and transcriptional reprogramming driven by global loss of negative transcriptional regulator H3K27 trimethylation (H3K27me3). Loss of H3K27me3 is an initiating event in gliomagenesis. This disease lacks appropriate models to predict disease biology and response to treatment. Therefore, we developed a novel syngeneic H3K27M mouse model. An unbiased integrated systems biology approach identified that H3K27M but not isogenic controls relied on the amino acid methionine and the enzyme Methionine Adenosyltransferase 2A ( MAT2A ). MAT2A is a central regulator of one-carbon metabolism by converting methionine to S-adenosylmethionine (SAM), the universal methyl-donor for protein and nucleotide methylation reactions. In complementary genetic approaches, we applied these findings to patient-derived cell lines with the H3K27M mutation. We hypothesize that MAT2A abrogation, genetic/pharmacological, would alter DMG viability by disrupting the methylome. The current MAT2A sensitivity paradigm is based on Methylthioadenosine Phosphorylase ( MTAP ) deletion through a synthetic lethal mechanism. We provide a novel mechanism whereby H3K27M cells are sensitive to MAT2A loss, independent of MTAP and through Adenosylmethionine Decarboxylase 1 (AMD1) overexpression disrupting MAT2A regulation. This results in H3K27M cells having lower MAT2A protein levels, conferring a sensitivity by inhibiting residual MAT2A. Genetic/pharmacological aberrations to MAT2A resulted in reduced proliferation. Parallel H3K36me3 ChIP and RNA-sequencing identified loss of oncogenic and developmental transcriptional programs associated with MAT2A loss. In vivo syngeneic and patient-derived xenograft models with both inducible MAT2A knockdown or methionine restricted diets showed extended survival. These results suggest novel interactions between methionine metabolism and the epigenome of H3K27M gliomas and provide evidence that MAT2A, presents exploitable therapeutic vulnerabilities in histone mutant gliomas.